Redox-associated messenger RNAs identify novel prognostic values and influence the tumor immune microenvironment of lung adenocarcinoma - Zhao, Chen; Xiong, Kewei; Bi, Dong; Zhao, Fangrui; Lan, Yanfang; Jin, Xiaorui; Li, Xiangpan (Frontiers in Genetics, 2023)
Background Imbalance of redox homeostasis participates in the tumorigenesis, proliferation and metastasis, which results from the production of reactive oxygen species (ROS). However, biological mechanism and prognostic significance of redox-associated messenger RNAs (ramRNAs) in lung adenocarcinoma (LUAD) still remain unclear. Methods Transcriptional profiles and clinicopathologic information were retrieved from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) of LUAD patients. 31 overlapped ramRNAs were determined and patients were separated into three subtypes by unsupervised consensus clustering. Biological functions and tumor immune-infiltrating levels were analyzed then differentially expressed genes (DEGs) were identified. TCGA cohort was divided into a training set and an internal validation set at a ratio of 6:4. Least absolute shrinkage and selection operator regression was utilized to compute the risk score and determine the risk cutoff in the training set. Both TCGA and GEO cohort were distinguished into a high-risk or low-risk group at the median cutoff then relationships of mutation characteristics, tumor stemness, immune differences and drug sensitivity were investigated. Results Five optimal signatures (ANLN, HLA-DQA1, RHOV, TLR2 and TYMS) were selected out. Patients in the high-risk group had poorer prognosis, higher tumor mutational burden, overexpression of PD-L1 and lower immune dysfunction and exclusion score compared with low-risk group. Cisplatin, docetaxel and gemcitabine had significantly lower IC50 in the high-risk group. Conclusions This study constructed a novel predictive signature of LUAD based on redox-associated genes. Risk score based on ramRNAs served as a promising biomarker for prognosis, TME and anti-cancer therapies of LUAD.